Lernen und Verbesserung von Sporttechniken durch Symmetrisierung der Bewegungen - Starosta, W. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
The human perfection of the movement knows no limit. By looking at the huge development we did the past years the question comes up if we haven't reached the end of the human possibilities? An answer to this question is difficult. It got even worse because the put up hypothesis in the area could seldom get con-firmed. Once for sure the recources we used are almost drained and for the progress we need new ones. One recource could be the symmetrization of the movement, which means that assymmetric movements must be changed into symmetric movements. Such a claim needs proof. To get the proof an experi-ment was carried out and literatur was studied. The aim of this work was to get some answers to: 1. Is symmetrization a recource for further human movement possibilities? 2. What kind of impact has the goal orientated and systematically symmetriza-tion of the movement on the technique of several kinds of sports? 3. Do the processes of symmetrization of the movement improve the athletic results? The experiment was done at 1641 people mostly worldclass athlets from judo, fig-ure skating and track and field athletics. The main method was observation and educational experiments which were done at 5 athletic disciplins (track and field athletics, Basketball, Soccer, ski downhill, figure skating). This work gives an overall view over own experimental results and other authors. It presents the re-sults of a planed and systematically realized symmetrization process and the re-sults from short lasting symmetrization attempt of the athlets and their coaches. Besides descriptions from symmetrization effects in objectives categories, this work also shows mutual dependences of symmetrization and sports events. By giving this an universal character that every human is surrounded by relations of symmetrization of its movement, which means that he is forced to find the balance of the ability of both body sides, I suggest a new concept for teaching movements.